A cross-sectional study: an assessment of low muscle mass and osteoporosis in type 2 diabetes mellitus patients with a high glycated hemoglobin level - Lingna Fang; Shao Zhong; Dan Ma; Chong Li; Yanmin Hao; Yan Gao; Li Zhang; Liwen Shen (SAGE Publishing, 2021)
Background: Low muscle mass and osteoporosis are commonly observed in individuals with type 2 diabetes mellitus (T2DM). We investigated the prevalence of low muscle mass and osteoporosis in patients with T2DM who had high glycated hemoglobin (HbA1c) levels. Methods: We included 187 Chinese patients with T2DM who were aged ⩾50 years and evaluated their body composition using dual-energy X-ray absorptiometry. We measured levels of fasting blood glucose, HbA1c, B collagen-specific sequences (B-CTX), osteocalcin (OC), propeptide of type 1 procollagen (P1NP), and 25-hydroxy vitamin D. Results: Of the total patients, 82 were men and 105 were women. The prevalence rates of low muscle mass, osteopenia, and osteoporosis were 35.8%, 38.0%, and 31.0%, respectively. The prevalence rate of low muscle mass was significantly higher in women with HbA1c levels >9.0% than in those with HbA1c levels <9.0%. The prevalence rates of osteopenia and osteoporosis in men with HbA1c levels >9.0% differed significantly from those with HbA1c levels <9.0%. The appendicular skeletal muscle mass index (ASMI), trunk muscle mass, lumbar spinal bone mineral content (BMC), lumbar spine BMD, femoral BMC, and femoral BMD were significantly decreased, and the serum levels of B-CTX, OC, and P1NP were significantly increased in patients with T2DM who had osteoporosis. The ASMI was associated with osteopenia/osteoporosis in men and women with T2DM. Conclusions: In patients with T2DM, high HbA1c levels were associated with higher prevalence rates of low muscle mass in women and osteoporosis in men, and ASMI was a risk factor of osteoporosis.